2011
DOI: 10.3415/vcot-10-06-0084
|View full text |Cite
|
Sign up to set email alerts
|

A review of extra-articular prosthetic stabilization of the cranial cruciate ligament-deficient stifle

Abstract: Extra-articular prosthetic stabilization techniques have been used as a method of stabilization of the cranial cruciate ligament (CrCL)-deficient stifle for decades. During extra-articular prosthetic stabilization, the prosthesis is anchored to the femur and tibia, and tensioned in the attempt to resolve femorotibial instability. The position of the anchor points of the prosthesis is crucial for restoring a normal range of joint motion and mitigating alterations in prosthesis tension during motion. Recently de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
62
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 78 publications
(145 reference statements)
2
62
0
11
Order By: Relevance
“…Evidence shows that current best available configurations are unable to maintain joint stability when physiologic loads are applied . All tests performed in our study showed evidence of superior biomechanical characteristics of double‐loop double‐crimp configurations (2L2C= and 2L2CX) when compared to previously recommended best configurations (2L1C and W1C) . Double‐loop double‐crimp configurations were the only ones able to consistently resist forces >600 N in all tests before failing.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Evidence shows that current best available configurations are unable to maintain joint stability when physiologic loads are applied . All tests performed in our study showed evidence of superior biomechanical characteristics of double‐loop double‐crimp configurations (2L2C= and 2L2CX) when compared to previously recommended best configurations (2L1C and W1C) . Double‐loop double‐crimp configurations were the only ones able to consistently resist forces >600 N in all tests before failing.…”
Section: Discussionmentioning
confidence: 57%
“…Long‐term joint stability is provided by periarticular fibrosis secondary to the surgical procedure and implanted material . It has been suggested that, for the surgical procedure to be effective, the suture material must withstand tension before failure for a minimum of 8 weeks with variability between dogs …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Extracapsular stabilization (ECS) is a common surgical procedure for cranial cruciate ligament (CrCL) deficiency . Lateral ECS transiently controls hyperextension, cranial drawer motion, and internal rotation of the tibia while periarticular fibrosis progresses .…”
mentioning
confidence: 99%